Materials and processing issues in vertical GaN power electronics. (May 2018) - Hu, Jie; Zhang, Yuhao; Sun, Min; Piedra, Daniel; Chowdhury, Nadim; Palacios, Tomás
Abstract: Silicon-based power devices are reaching their fundamental performance limit. The use of wide-bandgap semiconductors with superior material properties over silicon offers the potential for power electronic systems with much higher power densities and higher conversion efficiency. GaN, with a high critical electric field and carrier mobility, is considered one of the most promising candidates for future high-power, high frequency and high temperature applications. High voltage transistors and diodes based on both lateral and vertical structures are of great interest for future power electronics. Particularly, vertical GaN power devices have recently attracted increasing attention due to their many unique properties. This paper reviews recent progress and key remaining challenges towards the development of high-performance vertical GaN transistors and diodes with emphasis on the materials and processing issues related to each device architecture.